The Afrotropical species of Habritella Girault & Dodd (Hymenoptera: Pteromalidae) - Mitroiu, Mircea-Dan (European Journal of Taxonomy, 2022)
The previously endemic Australian genus Habritella Girault & Dodd, 1915 is reported for the first time in the Afrotropical region with four new species: H. africana sp. nov., H. mandibulata sp. nov., H. noyesi sp. nov., and H. viridifrons sp. nov. The males of Habritella are described for the first time. A new generic synonymy and combination are also proposed: Ezgia Koçak & Kemal, 2008 syn. nov. and H. stylifera (Bouček, 1988) comb. nov. Habritella is redescribed to accommodate the newly discovered and transferred species. An illustrated key to the Afrotropical species is provided.